'The Protected Disclosures Act 2000: limitation on the defamation law in South Africa' - Liwanga, Roger-Claude (School For Advanced Legal Studies, 2025)
Freedom of expression is constitutionally protected by the 1996 Constitution of South Africa. The constitution makes special provision to include freedom of the press and other media, freedom to receive or impart information or ideas, freedom of artistic creativity, academic freedom and freedom of scientific research. [FN11 However, the scope of freedom of expression does not cover the propaganda for war, incitement of imminent violence and advocacy of hatred based on race, ethnicity, gender or religion. [FN21 While freedom of expression constitutional protected, it is not the paramount value. It is limited as well by section 36 of Constitution, with the possibility of one being charged with defamation. Defamation is a public communication that tends to injure the reputation of another. [FN31 It includes both libel (written defamatory statement) and slander (oral ones). [FN41 Most jurisdictions, including South African, allow legal actions, civil and/or criminal against the defamatory statement. In the Court, therefore, in order to be found innocent, the defendant has to establish the "truth" of his/her statement. Failing to do so implies his/her liability and/or guilt.